An Atom-Efficient Direct Regioselective N(τ)-Allylation of Histidine Derivatives - Halland, Nis (Synlett, 2012)
Protected N(τ)-allylhistidine has been been prepared by the first direct regioselective allylation procedure using the sterically bulky N(α)-Boc protection group to shield N(π) and thereby inducing regioselectivity. This afforded the N(τ)-allyl protected histidine building block in excellent yields without loss of optical purity.
Keywords: histidine; allylation; regioselectivity; amino acid; alkylation